Penggunaan Chatbot dan E-Service Quality Terhadap Kepuasan dan Loyalitas Konsumen pada UMKM Digital di Kabupaten Pasuruan - Abdul Hafidz Maulidan; Miftahul Huda (Economic Reviews Journal, 2024)
This study aims to identify the effect of using chatbots and e-service quality on consumer satisfaction and loyalty in Digital MSME in Pasuruan Regency, This type of research is explanatory research with a quantitative approach. the data collection technique used is a questionnaire distributed offline. The sample used in the study was 116 respondents with a purposive sampling method, and the analysis results used a variant-based structural equation model Partial Least Square (PLS). Based on the results of this study, it can be seen that the use of chatbots has a positive and significant effect on satisfaction, the use of chatbots has a positive and significant effect on consumer loyalty, e-service quality has a positive and significant effect on satisfaction, e-service quality has a positive and significant effect on consumer loyalty, satisfaction has a positive and significant effect on consumer loyalty.